공격 행동 인식 및 중재를 위한 IMU 기반 웨어러블 시스템 개발 - 정우순(Woosoon Jung); 정규만(Kyunman Jeong); 류정탁(Jeong Tak Ryu); 박경옥(Kyoung-Ock Park); 오유수(Yoosoo Oh) (스마트미디어저널, 2024)
The biggest type of behavior that prevents people with developmental disabilities from entering society is aggressive behavior. Aggressive behavior can pose a threat not only to the personal safety of the person with a developmental disability, but also to the physical safety of others. In this study, we propose a wearable system using a low-power processor. The proposed system uses an IMU (Inertial Measurement Unit) to analyze user behavior, and when attack behavior is not detected for a certain period of time through an LED array attached to the developed system, an interesting LED is displayed. By expressing patterns, we provide behavioral intervention through compensation to people with developmental disabilities. In order to implement a system that must be worn for a long time in a power-limited environment, we present a method to optimize performance and energy consumption across all stages, from data preprocessing to AI model application. 발달장애인의 사회 진입을 막는 가장 큰 행동 유형은 공격 행동이다. 공격 행동은 발달장애인 자신의 안전뿐만 아니라 타인의 신체적 안전에도 위협이 될 수 있다. 본 연구에서는 저전력 프로세서를 활용한 웨어러블 시스템을 제안한다. 제안된 시스템은 IMU(Inertial Measurement Unit, 관성 측정 장치)가 적용되어, 사용자의 행동을 분석할 수 있으며, 개발된 시스템에 부착된 LED 배열을 통해 일정 시간 이상 공격 행동이 감지되지 않을 시, 흥미로운 LED 패턴을 표현하여 발달장애인에게 보상을 통한 행동 중재를 제공한다. 전원이 제한된 환경에서 장시간 착용해야 하는 시스템을 구현하기 위해 데이터의 전처리 과정부터 AI 모델 적용까지 전 단계에 걸쳐서 성능-에너지 소모 간 최적화 방법을 제시한다.